ROLA MOTYWACJI W PROCESIE UCZENIA SIĘ JĘZYKA PRZEZ UCZNIÓW Z DOŚWIADCZENIEM MIGRACJI – METODA JES-PL - Pamuła-Behrens, Małgorzata; Morena, Katarzyna (Neofilolog, 2019)
An increasing number of immigrant students pose new challenges for the Polish school. The immigrant groups consist of foreign children, but also Polish children who migrate with their parents. Their adaptation to a new place and integration are not always easy. These children do not only need professional support from the school and its staff, but also from Polish students. The key to succeeding in this complex process is to learn the language and culture of the country of settlement. Acquisition of this knowledge is conditioned by a motivation to face the Other, the language and culture. The purpose of the paper is to explore the role of motivation to learn the new language and culture of the country of settlement. In particular, we focus on determinants of motivation in the context of language learning and problems immigrant and refugee students are faced with in a new country. We also present the JES-PL Method which aims to support the development of language and communication skills within an immigrant family in the context of school language education (JES).